Results and possible prospects of genetic technology in ophthalmology (literature review). Part 2. (Ukrainian Journal of Ophthalmology, 2025)
The emergence of fundamentally novel technological solutions in the field of gene therapy today, the formation of the priority and the development of genetic technologies create serious prerequisites for the beginning of a new Fusion era in ophthalmology in the near future. This review, in its second part, presents the results of fundamental and clinical studies on the use of genetic therapeutic strategies – gene replacement, gene suppression, genomic editing using CRISPR / Cas9 technology which have been used in ophthalmology over the past several years.
Keywords: small interfering RNAs; antisense nucleotides; CRISPR; gene therapy; retina